DEVELOPMENT POLICIES AND PARTNERSHIPS IN SOUTHERN EUROPE: EVIDENCE FROM VARNA AND BARI - Metaxas, Theodore (Revista Galega de Economía, 2015)
The aim of this research is to investigate through empirical and primary data the possibility of design and implementation of development policies and partnerships in the South Eastern Europe especially in the areas of Bari and Varna. Specifically, this research is based on data extracted from 183 SMEs firms of all the productive sectors which express their evaluations for the role of specific development policies to their competitiveness per sector but also the degree and dynamic of developing partnerships with the local and regional authorities. Further the findings of the analysis designate the important issues of regional economic development focusing on the ability of public authorities to design and implement effectively development policies in order to benefit the competitiveness of themselves and the firms as well as the special sensitive areas of Southeastern Europe which is a very interesting zone for research.